Importance of program integrity: outcome evaluation of a gender‐responsive, cognitive‐behavioral program for female offenders - Duwe, Grant (Criminology & public policy, 2015)
We used a quasi‐experimental design to evaluate the effectiveness of Moving On, a gender‐responsive, cognitive‐behavioral program designed for female offenders. Between 2001 and 2013, there were two distinct periods in which Moving On was administered with, and without, fidelity among female Minnesota prisoners. To determine whether program integrity matters, we examined the performance of Moving On across these two periods. By using multiple comparison groups, we found that Moving On significantly reduced two of the four measures of recidivism when it was implemented with fidelity. The program did not have a significant impact on any of the four recidivism measures, however, when it operated without fidelity.